2021
DOI: 10.1186/s12905-021-01180-0
|View full text |Cite
|
Sign up to set email alerts
|

Is the use of contraceptives associated with periodontal diseases? A systematic review and meta-analyses

Abstract: Background Previous studies indicated an impact of hormonal contraceptive use on oral health. This systematic review aimed to investigate the evidence supporting the impact of the use of hormonal contraceptives and periodontal diseases. Methods This study is based on Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) and based on the PECO acrostic. Inclusion criteria comprised observational studies including women (P), whic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 48 publications
0
4
0
Order By: Relevance
“…Steroid hormones can indirectly lead to changes in periodontal tissue [ 13 , 49 ], and the presence of estrogen and progesterone receptors has been demonstrated in the gingivae. Estrogen receptors are present in periosteal fibroblasts, fibroblasts scattered in the lamina propria, and fibroblasts and osteoblasts of the periodontal ligament [ 3 , 13 ].…”
Section: Discussionmentioning
confidence: 99%
“…Steroid hormones can indirectly lead to changes in periodontal tissue [ 13 , 49 ], and the presence of estrogen and progesterone receptors has been demonstrated in the gingivae. Estrogen receptors are present in periosteal fibroblasts, fibroblasts scattered in the lamina propria, and fibroblasts and osteoblasts of the periodontal ligament [ 3 , 13 ].…”
Section: Discussionmentioning
confidence: 99%
“…According to studies, the lamina propria, gingival keratinocytes, and gingival fibroblasts found in the periodontal ligament all have receptors for sex hormones, including estrogen and progesterone. 17 Therefore, periodontal tissue can be indirectly modulated by steroid hormones. In addition to encouraging an increase in tissue glycogen production and lowering keratinization of gingival epithelium, which reduces the epithelial barrier, estrogen can control collagen metabolism 8 , 9 and angiogenesis.…”
Section: Discussionmentioning
confidence: 99%
“… 47 However, more (longitudinal) studies using sensitive methodological approaches are necessary to further elucidate the relationship between periodontitis and the HPA axis and its effector cortisol. 48 In addition, excessive or prolonged stress may be associated with more severe immune system dysregulation with regard to systemic inflammation, 19 , 24 , 49 which is thought to be the link between periodontitis and common comorbidities of periodontitis, such as coronary artery disease, osteoporosis, diabetes, and immune disorders (eg, rheumatoid arthritis). 50 , 51 , 52 …”
Section: Pni In Oral Medicinementioning
confidence: 99%